THE ROLE OF HERMENEUTICS IN UNDERSTANDING AND EXPLAINING (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The problem of understanding and its relation to knowledge (and explanation) has been discussed for a long time. It has not lost its importance today and is controversial in many ways. For example, while Dilthey described understanding as an introduction to the spiritual world of the author of the text, for Heidegger, understanding is a special relationship of a person to existence, a way of human existence in the world. According to Gadamer, understanding the culture of the past is inextricably linked to understanding the interpreter himself. Therefore, the subject of understanding is not the meaning embedded by the author in the text, but the material content (the "essence of the work"), which must be comprehended by this text. At the same time, according to Gadamer, any understanding is a problem of language: it is achieved (or not achieved) in the "medium of language" and does not require proof.